2015
DOI: 10.3109/00207454.2015.1059836
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in brain ischemia

Abstract: Endoplasmic reticulum (ER) stress is an intricate mechanism that mediates numerous responses during brain ischemia, thus being essential to determine the fate of neurons. In recent years, studies of the mechanisms of brain ischemic injury have centered on ER stress, glutamate excitotoxicity, dysfunction of mitochondria, inflammatory reactions, calcium overload and death receptor pathways. The role of ER stress is highly important. In addition to resulting in neuronal cell death through calcium toxicity and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…Glutamate acts via different types of glutamate receptors and thereby influences cell signaling cascades and elevates intracellular calcium in neurons. Increased ER stress is linked to brain ischemia (Su and Li, 2016) and to excitotoxic injury as studied by the use of the glutamate receptor agonist, kainic acid (Sokka et al, 2007; Putkonen et al, 2011). Salubrinal that is a specific inhibitor of the eIF2α phosphatase, PP1/GADD34 (Boyce et al, 2005) and was found to protect neurons against excitotoxicity in rat hippocampus and after cerebral ischemia induced by 15 min of brain vessel occlusion in gerbils (Sokka et al, 2007; Anuncibay-Soto et al, 2016).…”
Section: Upr In Neurodegenerative Disordersmentioning
confidence: 99%
“…Glutamate acts via different types of glutamate receptors and thereby influences cell signaling cascades and elevates intracellular calcium in neurons. Increased ER stress is linked to brain ischemia (Su and Li, 2016) and to excitotoxic injury as studied by the use of the glutamate receptor agonist, kainic acid (Sokka et al, 2007; Putkonen et al, 2011). Salubrinal that is a specific inhibitor of the eIF2α phosphatase, PP1/GADD34 (Boyce et al, 2005) and was found to protect neurons against excitotoxicity in rat hippocampus and after cerebral ischemia induced by 15 min of brain vessel occlusion in gerbils (Sokka et al, 2007; Anuncibay-Soto et al, 2016).…”
Section: Upr In Neurodegenerative Disordersmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress resulting from accumulation of unfolded and misfolded proteins within ER lumen has been reported to account for the neuronal death induced by cerebral ischemia, hypoxia, and trauma . Mild ER stress (unfolded protein response) exerts protection against cell damage, whereas sustained ER stress leads to cell death . Therefore, ER stress plays dual roles in regulation of cell destiny.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ER stress plays dual roles in regulation of cell destiny. Under condition of ER stress, GRP78, ATF6, phosphor‐PERK, and phosphor‐IRE1 are upregulated and thus regarded as the markers of ER stress . Although accumulating evidence has shown that ER stress contributes to cell death via induction of apoptosis and lethal autophagy, its role in the occurrence of parthanatos still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the upregulation of ERS-related transcription factors, including glucose-regulated protein (GRP)78 and CCAAT-enhancer-binding homologous protein (CHOP) have been identified (11,12). The involvement of ERS has been widely observed in the brain pathogenesis of neurological disorders and neurodegenerative diseases, including cerebral ischemia, Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis (9,13,14). Nonetheless, to the best of Edaravone improves spatial memory and modulates endoplasmic reticulum stress-mediated apoptosis after abdominal surgery in mice our knowledge, the regulatory role of ERS in the brain damage of POCD has not been described.…”
Section: Introductionmentioning
confidence: 99%